(untitled) - Marja Urpo; Suvi Eskola; Tarja Suominen; Mervi Roos (University of Ostrava, 2021)
Aim: This paper aims to analyse perioperative nurses' views of teamwork through team membership, team functionality, team cohesion, and team members' professionalism. Design: A descriptive, cross-sectional study. Methods: A questionnaire was sent to perioperative nurses working in one hospital district in Finland (n = 96). Data was collected by the Teamwork Scale and statistically analysed. Results: Perioperative nurses experienced teamwork positively. Team membership was associated with primary operating room (OR) role, engagement in the workplace, and perceived work empowerment. Team functionality was associated with combined OR role, working experience in healthcare, working experience as a perioperative nurse, and working shift. Team cohesion was associated with working shift and engagement in the workplace. Team members' professionalism was associated with engagement in the workplace, employment, and perceived work empowerment. Conclusion: Perioperative nurses' primary OR role and working shift had several connections to teamwork. This should be taken into careful consideration by OR managers in their daily work.